Protective Effect of Angiotensin 1–7 on Sarcopenia Induced by Chronic Liver Disease in Mice - Gonzalez-Rojas, A; Cabello-Verrugio, C; Abrigo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Sarcopenia associated with chronic liver disease (CLD) is one of the more common extrahepatic features in patients with these pathologies. Among the cellular alterations observed in the muscle tissue under CLD is the decline in the muscle strength and function, as well as the increased fatigue. Morphological changes, such as a decrease in the fiber diameter and transition in the fiber type, are also reported. At the molecular level, sarcopenia for CLD is characterized by: (i) a decrease in the sarcomeric protein, such as myosin heavy chain (MHC); (ii) an increase in the ubiquitin–proteasome system markers, such as atrogin-1/MAFbx1 and MuRF-1/TRIM63; (iii) an increase in autophagy markers, such as LC3II/LC3I ratio. Among the regulators of muscle mass is the renin-angiotensin system (RAS). The non-classical axis of RAS includes the Angiotensin 1–7 [Ang-(1-7)] peptide and its receptor Mas, which in skeletal muscle has anti-atrophic effect in models of muscle wasting induced by immobilization, lipopolysaccharide, myostatin or angiotensin II. In this paper, we evaluated the effect of Ang-(1-7) on the sarcopenia by CLD in a murine model induced by the 5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) hepatotoxin administered through diet. Our results show that Ang-(1-7) administration prevented the decline of the function and strength of muscle and increased the fatigue detected in the DDC-fed mice. Besides, we observed that the decreased fiber diameter and MHC levels, as well as the transition of fiber types, were all abolished by Ang-(1-7) in mice fed with DDC. Finally, Ang-(1-7) can decrease the atrogin-1 and MuRF-1 expression as well as the autophagy marker in mice treated with DDC. Together, our data support the protective role of Ang-(1-7) on the sarcopenia by CLD in mice. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.